Kajian Literatur: Perawatan Mulut sebagai Intervensi Pencegahan Ventilator-Associated Pneumonia pada Pasien Kritis - Nindya Rachma Gardhika Sari; Reni Sulung Utami (Holistic Nursing and Health Science, 2020)
Introduction: Ventilator-Associated Pneumonia (VAP) is a nosocomial pneumonia which develops after the patient received 48 hours of mechanical ventilation intubation. VAP raises various problems such as prolong length of stay and ventilator time, increase treatment costs, and increase risk of death. Appropriate and effective oral care is one of the nursing interventions that can reduce the incidence of VAP. The aim of this study was to identify procedure of oral care for prevention of VAP in critical patients. Methods: This research method is a literature review. Literature is searched through electronic database such as EBSCOhost, Scopus, Science Direct, and Proquest. The inclusion criteria of article were randomized controlled trials or randomized clinical trial designs, evaluate oral care effects on the prevention of VAP in critically ill patients, full text articles and publication years from January 2013 to May 2020. Results: Search results found as many as 38 articles, but only 9 articles were eligible to be reviewed. This review indicate that oral care has a significant effect on the prevention of VAP. The combination of toothbrush and swab is the most appropriate equipment. Chlorhexidine 2% was the most influential solution in reducing the incidence of VAP, while the frequency of oral care was most effective when adjusted to the results of the Back Oral Assessment Score (BOAS). Conclusion: This result reinforces the use of chlorhexidine in the oral care of mechanically ventilated patients. Oral care assessment needs to be done by nurses to guide in determining the frequency of oral care.